Academic Supervision Model In Improving Teacher Performance - Rusdiman AB; Paningkat Siburian; Saut Purba; Osberth Sinaga (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study describes the principal's supervision model in improving teacher performance, the stages of principal's supervision in improving teacher performance, and the obstacles faced in the implementation of principal's supervision in improving teacher performance. This research is a descriptive qualitative research with a pedagogical approach, a psychological approach, a sociological approach and a managerial approach. The research was conducted at SMK Negeri 1 Bireuen. Data sources are primary sources and secondary sources. Data collection techniques used observation, interviews, and documentation. The research instruments were interview guides, observation sheets and documentation. The data is processed by editing, coding, and tabulating. The data were analyzed by data reduction, data presentation, and drawing conclusions. The validity of the data was tested through technical triangulation and source triangulation. The results showed that the supervision models used were conventional models, artistic models, scientific models and clinical models. The stages of supervision are the planning stage including socialization, explaining the supervision indicators, and making a schedule, the implementation stage includes pre-observation, observation and post-observation activities, and the last is the follow-up stage. Obstacles to the implementation of supervision are the broad managerial scope of the principal, teachers are less prepared for learning, the subjectivity of supervisory teachers is still high, there are frequent replacements of principals, limited facilities and infrastructure, and lack of teacher discipline.